Human capital as the main source of socio-economic growth of the country (Journal of Economic Research & Business Administration, 2022)
The modern stage of development of postmodern society is characterized by the growing role ofeducation, training and general human culture. Based on a study of the economies of all countries, expertsfound that only 16% of economic growth is provided by physical capital, 20% – natural and 64%– human capital. The success of developed countries is determined by their attitude to human capital,from the point of view of public policy. Investments in the social sphere, previously considered nonrefundableexpenses, are now considered as investments in the future prosperity of the country.The purpose of the article is to determine, based on world experience, the role of human capital inthe context of socio–economic growth of the country and the consequences of the Covid-19 pandemicin its development.Over the years of independence, Kazakhstan has achieved economic success by increasing oil andgas exports and increasing productivity. However, in recent years, our country has lagged behind insome key indicators of competitiveness. In addition, the COVID-19 pandemic has seriously underminedKazakhstan’s achievements in human capital development. The author examines the investment policyof the human capital system of developed countries and comes to the conclusion that in order to achievesustainable growth of the country’s economy, modernization of the human capital development systemis necessary.The research area of the article involves the use of interdisciplinary approaches to study the problemand fulfill the set goals and objectives. To ensure the complexity of the study, it is proposed to use acombination of economic, statistical, systemic and comparative analysis.Analyzing the world experience, the authors made a number of proposals to improve and developthe country’s human capital as the main factor of socio-economic growth.The value of the conducted research lies in the possibility of their use in the development of a scientificand methodological basis for decision-making in the field of human capital management in theface of negative scenarios of the situation, as well as in the development of a policy of socio-economicdevelopment of the regions of Kazakhstan, the strategy of sustainable development of Kazakhstan.Key words: human capital, economic growth, social development, investments, national values,development strategy.